Identification and functional analysis of serine protease inhibitor gene family of Eocanthecona furcellata (Wolff) - Zhang, Man; Dai, Zhenlin; Chen, Xiao; Qin, Deqiang; Zhu, Guoyuan; Zhu, Tao; Chen, Gang; Ding, Yishu; Wu, Guoxing; Gao, Xi (Frontiers in Physiology, 2023)
The predatory natural enemy Eocanthecona furcellata plays a crucial role in agricultural ecosystems due to its effective pest control measures and defensive venom. Predator venom contains serine protease inhibitors (SPIs), which are the primary regulators of serine protease activity and play key roles in digestion, development, innate immunity, and other physiological regulatory processes. However, regulation mechanism of SPIs in the salivary glands of predatory natural enemies is still unknown. In this study, we sequenced the transcriptome of E. furcellata salivary gland and identified 38 SPI-genes named EfSPI1~EfSPI38. Gene structure analysis showed that these 38 EfSPIs genes contained 8 SPI domains, and according to their mode of action, they were divided into serpins, canonical inhibitors and alpha-2-macroglobulins (A2Ms), which were Serpin, TIL, Kunitz, Kazal, Antistasin, Pacifastin, WAP and A2M. We performed multiple sequence alignments, predicted hydrolytic active sites, and phylogenetic tree analysis of the identified EfSPIs members with SPIs of other species with known functions. Results showed that some EfSPIs may inhibit trypsin, chymotrypsin, and elastase, and some EfSPIs may be involved in autoimmune responses. Expression profile results showed that expression of different types of EfSPIs genes was different at different developmental stages. Most of EfSPIs genes were highly expressed in the egg stage. The EfSPI20, EfSPI21, EfSPI22, and EfSPI24 genes of the Pacifastin subfamily and the EfSPI35 gene of the A2M subfamily were highly expressed in the nymphal and adult stages, which was consistent with the real-time quantitative PCR (RT-qPCR) verification results. These five genes are positively correlated with each other and have a synergistic effect on E. furcellata. Tissue expression results also showed they were highly expressed in salivary glands.After interfering with the expression of EfSPI20 gene, survival rate and predatory amount of male and female adults significantly decreased. Taken together, we speculated that EfSPI20 was essential for the predation and digestion of E. furcellata, and the functions of other EfSPIs were discussed. Our findings provide valuable insights into the diversity of EfSPIs in E. furcellata and the potential functions of regulating their predation, digestion and innate immunity, which maybe of great significance for developing new pest control strategies.